Newly Design Porous/Sponge Red Phosphorus@Graphene and Highly Conductive Ni2P Electrode for Asymmetric Solid State Supercapacitive Device With Excellent Performance - Parveen, Nazish; Hilal, Muhammad; Han, Jeong In (Nano-Micro Letters, 2020)
Supercapacitors have attracted much attention in the field of electrochemical energy storage. However, material preparation, stability, performance as well as power density limit their applications in many fields. Herein, a sponge-like red phosphorus@graphene (rP@rGO) negative electrode and a Ni2P positive electrode were prepared using a simple one-step method. Both electrodes showed excellent performances (294 F g−1 and 1526.6 F g−1 for rP@rGO and Ni2P, respectively), which seem to be the highest among all rP@rGO- and Ni2P-based electrodes reported so far. The asymmetric solid-state supercapacitor was assembled by sandwiching a gel electrolyte-soaked cellulose paper between rP@rGO and Ni2P as the negative and positive electrodes. Compared to other asymmetric devices, the device, which attained a high operating window of up to 1.6 V, showed high energy and power density values of 41.66 and 1200 W kg−1, respectively. It also has an excellent cyclic stability up to 88% after various consecutive charge/discharge tests. Additionally, the device could power commercial light emitting diodes and fans for 30 s. So, the ease of the synthesis method and excellent performance of the prepared electrode materials mat have significant potential for energy storage applications. Highlights: 1 Three-dimensional phosphorus@graphene is established as a negative electrode and Ni2P as a positive electrode for asymmetric supercapacitor. 2 The supercapacitor shows higher performance than those of all Ni2P-based electrodes, which has an extended operating voltage window of 1.6 V, energy density of 41.66 Wh Kg−1 and rate capability of up to 88% after 5000 cycles.